2020
DOI: 10.3390/antibiotics9100705
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Outbreaks of Extended-Spectrum Beta-Lactamase-Producing Klebsiella Pneumoniae in Three Neonatal Intensive Care Units Using Whole Genome Sequencing

Abstract: Infections caused by extended-spectrum beta-lactamase-producing Klebsiella pneumoniae (ESBL-KP) are on a constant rise and are a noted cause of outbreaks in neonatal intensive care units (NICUs). We used whole genome sequencing (WGS) to investigate the epidemiology of consecutive and overlapping outbreaks caused by ESBL-KP in NICUs in three hospitals in close proximity. Clonality of 43 ESBL-KP isolates from 40 patients was determined by BOX-PCR. Short-read sequencing was performed on representative isolates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The clustered occurrence of some Klebsiella pneumoniae ( Kp ) strains suggests possible outbreaks and may provide clues about infection sources in this study. Strains ST35 and ST37, which were responsible for more than half of all GNB sepsis in this study, have been associated with MDR and reported to be sources of outbreaks within NICU settings outside sSA [ 59 61 ]. Both ST35 and ST37 have also been detected in the feces of healthy adults and animals in the community [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clustered occurrence of some Klebsiella pneumoniae ( Kp ) strains suggests possible outbreaks and may provide clues about infection sources in this study. Strains ST35 and ST37, which were responsible for more than half of all GNB sepsis in this study, have been associated with MDR and reported to be sources of outbreaks within NICU settings outside sSA [ 59 61 ]. Both ST35 and ST37 have also been detected in the feces of healthy adults and animals in the community [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 CTX-M-15 positive E. coli and K. pneumoniae have been reported to cause outbreaks in neonatal intensive care units (NICUs) worldwide. [9][10][11][12] Additionally, K. pneumoniae ST14 isolates expressing CTX-M-15 have been reported as being associated with neonatal sepsis in Tanzania between 2009 and 2010, as well as in Spain in 2008. 24,25 In Saudi Arabia, several studies have reported the dominance of CTX-M-15 genes among Enterobacteriaceae, 26,27 including in K. pneumoniae isolates associated with an NICU in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…ESBL-producing E. coli and K. pneumoniae have previously been reported to cause outbreaks of infection in neonatal intensive care units (NICUs). 11 , 12 However, to our knowledge, this is the first report of a CTX-M-15-positive E. coli and K. pneumoniae outbreak in the neonatal intensive care unit of a maternity hospital in Saudi Arabia. In this study, we retrospectively characterized 19-ESBL-positive E. coli , and 42-ESBL-positive K. pneumoniae isolates obtained from an outbreak of infection at a neonatal intensive care unit (NICU) in the Ha’il region of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 86%
“…ORFs were searched against the CARD and NCBI databases using DIAMOND BLAST [ 10 ]. Whole-genome sequencing (WGS) using both short-read and long-read technologies was used as previously described [ 11 ].…”
Section: Methodsmentioning
confidence: 99%